Inpatient Health Care Utilization in Children With Hemophilia Before and After the Joint Outcome Study Publication. Issue 5 (July 2019) - Drayton Jackson, Meghan; O'Brien, Sarah H.; Stanek, Joseph; Dunn, Amy L.; Kerlin, Bryce A.
Abstract : The "Joint Outcomes Study" (JOS) demonstrated improved joint outcomes for patients receiving primary prophylaxis versus on-demand therapy. The impact of primary prophylaxis on inpatient health care utilization is not well-defined. To evaluate changes in hospitalization care of children with hemophilia before and after the 2007 JOS publication, this study utilized the Pediatric Health Information System (PHIS) to evaluate admissions for patients with hemophilia A or B (age, 2 to 7) admitted between January 2002 and 2006 (pre-JOS) and January 2010 and 2014 (post-JOS). Discharge diagnosis codes and clinical transaction classifications were used to differentiate bleeding episodes, infections, bypass agent use, length of stay, and intensive care unit (ICU) management. Overall, admissions for bleeding episodes did not change (26.5% of admissions pre-JOS vs. 23.6% post-JOS, P= 0.10). However, admissions for suspected infections increased (3.0% of admissions pre-JOS vs. 7.2% post-JOS, P <0.01) while confirmed infections remained stable. Meanwhile, ICU utilization decreased (7.8% of admissions pre-JOS vs. 4.9% post-JOS, P< 0.01). The necessity for ICU care in children with hemophilia has decreased since publication of the JOS. However, expanded adoption of primary prophylaxis is associated with more hospitalizations for suspected systemic infections, likely due to utilization of central venous catheters to deliver clotting factor concentrates.